Three years in Korea: a brief history of I US Corps, 12 September 1950-to-September 1953. - Historical Section, G-3, I Corps
This history, while limited in scope to the barest essentials, is one intertwined with the military history of the nation over the past ninety-one years and five major wars, for I U.S. Corps has indeed been "first" in every one of them. Its troops have fought over mountain a and swamps, plains and jungles, in weather that ranged from sub-tropical to arctic. Only one characteristic has been common to all of its numerous engagements - success, the accomplishment of its missions. This is not to imply that the going has ever been easy. There have been setbacks and severe trials, but in the end has come victory. This heritage is one that those who have served with I U.S. Corps proudly bear.